DETERMINANTS OF TAXPAYER COMPLIANCE: ROLE OF LOVE OF MONEY, MACHIAVELLIANISM, WHISTLEBLOWING SYSTEM, RELIGIOSITY, AND TRUST IN GOVERNMENT - Amir Hidayatulloh (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
The purpose of this study is to analyze the factors that influence taxpayer compliance and the role of the religiosity variable on taxpayer compliance, both as an independent variable and a moderating variable. The respondent of this research is an entrepreneur who has a Taxpayer Identification Number. Data were obtained by distributing questionnaires to respondents who met the criteria. Data analysis of this research uses Partial Least Square with WarpPLS tool. Respondents of this study amounted to 87 people. This study found that taxpayer compliance is influenced by love of money, machiavellianism, whistleblowing system, and trust in the government. Meanwhile, religiosity has no effect on taxpayer compliance. This study also found that religiosity moderated the effect of Machiavellianism on taxpayer compliance, but did not moderate the effect of love of money on taxpayer compliance.